A systematic review of empirical studies pertaining to Lean, Six Sigma and Lean Six Sigma quality improvement methodologies in paediatrics. (11th December 2020) - Samanta, Alok Kumar; Varaprasad, G.; Padhy, Ramakrushna
Lean, Six Sigma and Lean Six Sigma (LSS) are the quality improvement (QI) methodologies that have proved their merits in healthcare organisations since the 1990s. The aim of this paper is to present a systematic review of literature on the implementation of these QI methodologies in paediatrics by using a three-phase systematic review process (SRP), i.e., planning, conducting and reporting. The literature search was carried out in Web of Science, Scopus, and PubMed for articles published until April 2019. The broad range of outcomes from SRP was collated into six common themes: time optimisation, motion reduction, error mitigation, dosage optimisation, efficiency enhancement, and revenue generation. It is suggested that researchers and practitioners in paediatrics need to understand these QI methodologies deeply and deploy these in a profound way to realise their true potential. This is the first systematic review to synthesise the implementation results of QI methodologies in paediatrics.